Stereotypes and tournament self-selection: A theoretical and experimental approach - Hernandez-Arenaz, Iñigo (European economic review, 2020)
We present a theoretical model in which agents have imperfect self-knowledge about their abilities and have to self-select into either a high-paying or a low-paying tournament. The model shows that negative (positive) stereotypes generate underrepresentation (overrepresentation) of stereotyped agents in the high-paying tournament even when the stereotype is false. This is because stereotypes affect self-assessment and consequently subsequent behavior. We call this mechanism self-stereotyping. We run a lab experiment in which we use subjects’ beliefs about the gender bias of a real-effort task to test the predictions of the theoretical model. The results of the experiment are in line with the predictions of the model for men but not for women, which partially validates the model and the self-stereotyping mechanism.